Adult Education opportunities for disabled persons in Iceland - Sibeso Imbula Sveinsson 1970- (2016)
Abstract This purpose of this paper is to review the status of adult education opportunities for persons with disabilities in Iceland. Considering that adult education for disabled persons has evolved and some changes have taken place compared to twenty years ago, this thesis begins with a theoretical analysis of quality of life in general for disabled people and its importance. The paper addresses the roles of self-determination and empowerment as key aspects and their role in quality of life in order to enable disabled people to take full control of their lives and participate fully in society as equal citizens. With these aspects in mind, I consulted professionals working in institutions providing different forms of education to adults with disabilities in different adult education school settings to get clear picture of the current situation, with emphasis on evaluating and learning about the available options. Academic development, attitudes and education services have evolved in recent years for people with disabilities, in relation to required basic needs for disabled people to live normal and independent lives. My conclusions gave a good picture of the actual situation of disabled people when it comes to adult education services and provided answers to my subject of study, showing that there are many adult education opportunities available, though accessibility and community attitudes can hinder participation of disabled adults in education programs if joint efforts by stakeholders are absent. In the other hand, education has great benefits as it contributes towards general quality of life.